2009
DOI: 10.1038/modpathol.2008.205
|View full text |Cite
|
Sign up to set email alerts
|

REG4 is associated with carcinogenesis in the ‘intestinal’ pathway of intraductal papillary mucinous neoplasms

Abstract: Subclassification of intraductal papillary mucinous neoplasms of the pancreas (IPMNs), based on morphological features and immunohistochemical profiles, has been proposed. Intestinal-type IPMNs frequently show moderate to severe dysplasia. Regenerating islet-derived family, member 4 (REG4) is associated with the adenoma-carcinoma sequence in colon cancer and it is also associated with intestinal phenotype. Therefore, to identify REG4 expression in IPMNs may be helpful to detect high-grade IPMNs. We also invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…Previous studies have identified markers specific for intestinal-type intraductal papillary mucinous neoplasm, including MUC2, CDX2, and REG4. 31 In the present study, we have identified CLDN4 as a novel marker for intestinal-type intraductal papillary mucinous neoplasm.…”
Section: Discussionmentioning
confidence: 59%
“…Previous studies have identified markers specific for intestinal-type intraductal papillary mucinous neoplasm, including MUC2, CDX2, and REG4. 31 In the present study, we have identified CLDN4 as a novel marker for intestinal-type intraductal papillary mucinous neoplasm.…”
Section: Discussionmentioning
confidence: 59%
“…These results are consistent with a demonstrated functional impact of Reg IV in pancreatic and some colon cancer cell lines, 23,31 although other studies have failed to show an effect of Reg IV modulation on colon cancer cell growth. 24,32 Although it has been shown that Reg IV expression is significantly correlated to Ki67 staining, 10 to date cell cycle analyses and modulation of cell cycle proteins have not been investigated in the context of Reg IV. We showed upregulation of cell cycle inhibitors, p21 and p27, consistent with the cell cycle profile we observed (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the importance of IR in glucose homeostasis, an ideal anti-IGF strategy would target both IGFIR and IR only in tumor cells. 40 Given the restricted expression profile of Reg IV in normal tissues seen by immunohistochemistry, [9][10][11][12][13][14][15][16][17][18] anti-Reg IV therapy might represent a way to target IR activation only in tumors.…”
Section: Cancer Cell Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…IPMNs can be classified into four types, intestinal, gastric foveolar, oncocytic and pancreatobiliary, based on their histology and expression of mucin proteins. IPMN progresses from benign pancreatic intraductal papillary mucinous adenoma (IPMA) to malignant pancreatic intraductal papillary mucinous carcinoma (IPMC) (2,3), however, the details of this process of carcinogenesis remain to be fully elucidated. In the present study, the factors affecting the carcinogenesis of IPMN were investigated.…”
Section: Introductionmentioning
confidence: 99%